Generalized proper efficiency and duality for a class of nondifferentiable multiobjective variational problems with V-invexity - Mishra S.K. (My University, 2025)
A Mond-Weir type dual for a class of nondifferentiable multiobjective variational problems in which every component of the objective function contains a term involving the square root of a certain positive semidefinite quadratic form, is considered and various duality results, viz. weak, strong, and converse duality theorems, are developed for conditionally properly efficient solutions. These results are obtained under V-invexity assumptions and its generalizations on objective and constraint functions. This work extends many results on variational problems established earlier. © 1996 Academic Press, Inc.